A “Minsky crisis” in a Stock-Flow Consistent model - Tarik Mouakil (Revue de la Régulation)
This study uses the Stock-Flow Consistent modelling approach to assess the relevance of Minsky’s demonstration of his financial instability hypothesis. We show that this demonstration, based on the assumption of a pro-cyclical leverage ratio, is incompatible with the Kaleckian analysis of profits endorsed by Minsky. Therefore we suggest replacing the assumption of a pro-cyclical leverage ratio with one of a pro-cyclical short-term borrowing, which also appears in Minsky’s work.